2012
DOI: 10.1063/1.4757505
|View full text |Cite
|
Sign up to set email alerts
|

Numerical solution of Lane-Emden equation using neural network

Abstract: This paper presents a numerical method based on neural network, for solving the Lane-Emden equations singular initial value problems. The numerical solution is given for integer case and non integer case. The non integer case is taken in the sense of Riemann-Liouville operators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Jalab et al [70] have shown a numerical method based on neural network, for solving the Lane-Emden equations singular initial value problems. The numerical solution has been given for integer case and non integer case.…”
Section: The Methods Have Been Proposed To Solve Lane-emden Type Equa...mentioning
confidence: 99%
“…Jalab et al [70] have shown a numerical method based on neural network, for solving the Lane-Emden equations singular initial value problems. The numerical solution has been given for integer case and non integer case.…”
Section: The Methods Have Been Proposed To Solve Lane-emden Type Equa...mentioning
confidence: 99%
“…Undoubtedly, the theory of existence holds a paramount position within the realm of fractional calculus. Researchers have also come up with many results on the solutions of existence and uniqueness to the initial and boundary value problems (BVPs) of FDEs in the sense of Riemann-Liouville and Caputo fractional derivatives, see ( [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the subject of numerical methods for solving fractional differential equations has gained prominence and has been discussed by several authors, including a series of papers [25][26][27][28][29][30][31] and references cited therein, which include some recent studies on the approximation method for differential equations of fractional order. El-Ajou et al [32] extended the application of the homotopy analysis method (HAM) to provide symbolic approximate solution for twopoint boundary value problems of fractional order.…”
Section: Introductionmentioning
confidence: 99%